2019
DOI: 10.1186/s12905-019-0715-4
|View full text |Cite
|
Sign up to set email alerts
|

Mixed methods assessment of women’s risk of intimate partner violence in Nepal

Abstract: BackgroundIntimate partner violence (IPV) is a significant public health issue that affects one in three women globally and a similarly large number of women in Nepal. Although important policy and programmatic steps have been taken to address violence against women in Nepal over the past decade, there is still a gap on IPV research in Nepal, particularly with regard to social norms.MethodsThis mixed-methods study used in-depth interviews with women and their husbands as well as baseline survey data from a clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 29 publications
3
30
1
Order By: Relevance
“…Most likely the reason sexual IPV is much higher at 18 months is due to underreporting at baseline and midline [28]. In comparison, a bigger What Works study that took place in Nepal around the same time as our study had much higher levels of IPV reporting: of the 1800 women surveyed from 36 clusters in three districts, 15.7% had reported physical violence, 18.1% (N = 325) sexual violence, and a quarter of them, 25.3% (N = 455) reported physical and/or sexual violence [49].…”
Section: Discussioncontrasting
confidence: 59%
“…Most likely the reason sexual IPV is much higher at 18 months is due to underreporting at baseline and midline [28]. In comparison, a bigger What Works study that took place in Nepal around the same time as our study had much higher levels of IPV reporting: of the 1800 women surveyed from 36 clusters in three districts, 15.7% had reported physical violence, 18.1% (N = 325) sexual violence, and a quarter of them, 25.3% (N = 455) reported physical and/or sexual violence [49].…”
Section: Discussioncontrasting
confidence: 59%
“…It is suggested that poor households where men are the only providers, men tend to be perpetrators of violence due to poverty-related stressors that lead to fighting over spending and women’s dependence on men [53]. Equally, where women are not economically disadvantaged, men have been found to resort into violence to reassert control [54, 55]. The pathway through which poverty influence partner violence can be interpreted in the context of power relations in that lack of financial resources and financial dependency on perpetrators increases AGYW’s vulnerability to partner violence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, women who have been abandoned by husbands or widowed and women who have been raped or cannot name the father of their child are unable to pass citizenship, as a right, to their Nepali‐born children (Allison, 2017). They are also affected by practices that seek to control, seclude and restrict them such as the custom of expecting young married women to remain at home and not to be seen out in the community (Clark et al, 2019; Ghimire et al, 2013; Morrison, Basnet, et al, 2018). Limited decision‐making powers, early marriage, early pregnancy, overwork and neglect negatively affect women's health (Adaeze Nwokolo et al, 2020; Marphatia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%